A study into the behaviour of various asset classes' returns and inflation in the Singapore context - Loh, Chong Ho (2014)
Inflation has always been a prevailing phenomenon which accompanies economic growth. However, inflation has many undesirable political and social effects and is of a major concern for nations worldwide. For investment analysis purposes, many studies have been done in the United States regarding the impact of inflation.